The Endcap Disc DIRC detector of PANDA - Föhl, K.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Götzen, K.; Krebs, M.; Lehmann, D.; Nerling, F.; Patsyuk, M.; Peters, K.; Schepers, G.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
At the international FAIR laboratory, an upcoming significant enlargement of the GSI installations near Darmstadt, Germany, the PANDA antiproton experiment will investigate fundamental questions of hadron physics in the charm quark energy range. Antiprotons in the 1.5 to15 GeV/c momentum range will interact with gas jet or pellet fixed targets. The Endcap Disc DIRC (Detection of Internally Reflected Cherenkov light) covers the forward endcap solid angle of the PANDA target spectrometer to positively identify charged kaons. Monte-Carlo simulations indicate that from 1 up to 4 GeV/c one can achieve kaon–pion separation with a separation power of at least 3 standard deviations. For the upcoming CERN test beam in August 2018 the read-out electronics has been upgraded to the TOFPET-ASIC Version 2.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Cherenkov light; DIRC; Particle identification